IEC 61850 Routable GOOSE and SV profiles over IP telecom networks - Saraiva, Diogo Emanuel Morgado (2019)
We live in an era where the consumption of energy rises to an almost immeasurable level, jeopardizing the balance of systems when a power failure in the electrical grid occurs. This brought the necessity of making it safer and intelligent, hence emerging the concept of Smart Grid. The IEC 61850 standard was initially designed to operate within substations, yet other potential developments glimpsed to operate not only within substations but also to the outside of them. Based on several communications protocols, including MMS, GOOSE and SV, the IEC 61850 provides the possibility of real-time data exchange, leading to cost savings, increased security and interoperability between different vendors’ devices. Addressing this issue, together with EFACEC and the Institute of Telecommunications of Aveiro, a key question emerged: What are the requirements for the communication between devices in different substations? This MSc dissertation aims to answer this question, as well as to analyse other possible technologies that are suitable at the time of its implementation. With this analysis, a specific technology stands out, the 4G-LTE. A study was conducted recurring to temporal diagrams of the messages, performing with both approaches as described in the standard. Either using the IP or VPN approach, different technologies such as ADSL, Optical Fibre, and the previously referred 4G-LTE were tested. Thereafter, the results of the study are analysed, obtaining this way the conclusions for each one of the approaches, as well for each of the different technologies studied. Last but not least, it is analysed which of the approaches will be more beneficial in the long-term, as well as the necessary future work that must be developed in the different areas of the presented standard.